2016
DOI: 10.1111/ijcp.12859
|View full text |Cite
|
Sign up to set email alerts
|

Utility of virtual unenhanced images and split-bolus injection using spectral multidetector CT for the assessment of renal cell carcinoma conspicuity and radiation dose

Abstract: Conspicuity with virtual unenhanced imaging and split-bolus injection from spectral multidetector CT is better than or equal to the conventional three-phase enhanced CT scan in showing the RCC, renal artery and renal vein, while the radiation dose can be reduced by 28.78%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Results from previous studies (7,10,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) have demonstrated variable attenuation error rates of VNC images, with the majority of these studies demonstrating a good correlation between the VNC and the unenhanced attenuation values of various anatomic regions with differences below 5 HU. However, some studies (21,26,27) have shown differences between VNC and unenhanced attenuation values of up to 10 HU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous studies (7,10,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) have demonstrated variable attenuation error rates of VNC images, with the majority of these studies demonstrating a good correlation between the VNC and the unenhanced attenuation values of various anatomic regions with differences below 5 HU. However, some studies (21,26,27) have shown differences between VNC and unenhanced attenuation values of up to 10 HU.…”
Section: Discussionmentioning
confidence: 99%
“…and VNC images when a second generation or newer DE CT system was used (10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The factors for this difference may be multifactorial, including different patient cohorts with different contrast media phases, patient size, and subjective image interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous variables were analyzed using unpaired t test, and categorical variables were analyzed by Mann-Whitney U test. 16 The Tukey-Kramer post hoc analysis was employed to evaluate the difference among different groups. 17 One-way analysis of variance (ANOVA) was employed to compare variables among more than 2 groups.…”
Section: Discussionmentioning
confidence: 99%